HOW GESTURE PROVIDES A HELPING HAND AND SUPPORTS CHILDREN’S LANGUAGE ACQUISITION - Ma'rifah Nurmala (Ana' Bulava: Jurnal Pendidikan Anak, 2020)
Children use gesture to refer to objects before they produce labels for these objects to convey semantic relations between objects before conveying sentences in speech. The gestural input that children receive from their or teacher shows that they provide models for their children for the types of gestures and gesture to produce, and do so by modifying their gestures to meet the communicative needs of their children. This article aims to discuss what we know about the impact of gestures on memorization of words. This article describes an explanation the form and example why using gesture would help educator and parent in supports children’s language development. More importantly, the gestures that parents and teachers produce, in addition to providing models, help children learn labels for referents and semantic relations between these referents and even predict the extent of children’s vocabularies several years later. The existing research highlights the important role parental even the teacher gestures play in shaping children’s language learning.